Pengaruh Harga Lokasi Dan Kualitas Layanan Terhadap Kepuasan Pengunjung Wisata Sumber Gentong - Fia Adilia Alfina Chuswondo; Muhammad Ridwan Basalamah; M Tody Arsyianto (UNIVERSITAS ISLAM MALANG, 2023)
Abstract The purpose of this study is to ascertain how Wisata Sumber Gentong customers perceive the impact of pricing, location, and service quality. Quantitative research is the method employed. Purposive sampling was used to collect samples using the Maholtra method, which multiplies the number of indicators by 5 to create a total of 85 respondents. Multiple linear analysis is the method of choice for data analysis. using the t test for partial testing and the F test for simultaneous testing. The findings of this study show that Wisata Sumber Gentong customer satisfaction is simultaneously significantly impacted, according to the results. While only somewhat, Wisata Sumber Gentong customers are significantly impacted by Price, Location, and Quality of Service. Keywords: Price, Location and Service Quality